Encoding youthful perspectives of the Anti-Communist Revolution - RUSU, Maria Smaranda (Studia Universitatis Babeș-Bolyai Digitalia, 2021)
Encoding youthful perspectives of the Anti-Communist Revolution” presents in a captivating manner two interviews dating back to the time in the history of Romania when the country was struggling with the Communist revolution which started in Timisoara. The perspective in which this information is described is the XML language. In order to simplify the data and to make it more accesible, there were used tags in a scheme. By using this method, the readers can have a better understanding of the text while having an over-all look upon the discussed historical issue.